DOP77 Is durable remission achievable after ileocolic resection for Crohn's disease ? Long-term results of a prospective multicentric cohort study of the GETAID Chirurgie. (30th January 2023) - Abdalla, S; Benoist, S; Maggiori, L; Lefevre, J; Denost, Q; Cotte, E; Germain, A; Beyer-Berjot, L; Desfourneaux, V; Rahili, A; Duffas, J P; Pautrat, K; et al.
Abstract: Background: Most of the patients undergoing bowel resection for Crohn's disease (CD) develop postoperative recurrence requiring medical treatment intensification or surgery. Is there a subgroup of patients for which surgery allows durable remission? Methods: In this retrospective follow-up study, we collected data from 592 patients undergoing ileocolic resection for CD who were included from 2013 to 2015 in a prospective nation-wide cohort of the GETAID Chirurgie group. Patients with follow-up superior to 36 months were included. Primary outcome was durable remission, defined as the absence of endoscopic recurrence (Rutgeerts ≥i2) and/or absence of medical treatment intensification. Uni- and multivariate analyses of the predictive factors for durable remission were carried out. Results: Among 268 included patients, 158 (59%) had a B2 stricturing phenotype, 92 (34%) had a B3 penetrating phenotype and 18 (7%) had a non-stricturing non-perforating phenotype (Montreal classification). One hundred and eighty-eight patients (70%) had a primary ileocolic resection. One hundred and sixty-seven patients (66%) had postoperative medical treatment to prevent postoperative recurrence (Table 1). After a median follow-up of 85 (36-104) months, 52 patients (19%) had a durable remission, among which 24 (46%) had no medical treatment and 28 (54%) maintained the same postoperative prophylactic treatment, including anti-TNF therapy in 15 patients (54%) (Table 2). Durable remission rate was significantly increased in B1 phenotype vs B2/B3 (n=7/18 ;39% vs n=45/250; 18%, p=0.030) and in primary ileocolic resection vs redo ileocolic resection (n=43/184 ; 23% vs n=9/80 ; 11%, p=0.023). In multivariate analysis, B1 phenotype was an independent predictive factor for durable remission (OR=3.59, IC95%[1.13-11.37], p=0.030) (Table 3). Conclusion: These long-term data obtained from a nation-wide prospective cohort are in line with those of a randomised controlled trial (LIR!C) and show that durable remission is obtained in nearly 40% of CD patients with non-stricturing non-penetrating phenotype operated for CD refractory to medical treatment. This important result should be considered when medical treatment intensification versus surgery is discussed in these patients.